Nitrogen removal and bacterial mechanism in a hybrid anoxic/oxic baffled reactor affected by shortening HRT in treating manure-free piggery wastewater. (September 2021) - Li, Jianzheng; Deng, Kaiwen; Li, Jiuling; Liu, Min; Meng, Jia
Abstract: A hybrid anoxic/oxic baffled reactor (HAOBR) with four compartments was constructed to treat manure-free piggery wastewater which was characterized by high ammonium (NH4 + -N) and low chemical oxygen demand (COD) to total nitrogen (TN) ratio. To evaluate the suitable volumetric removal rate, hydraulic retention time (HRT) was decreased from 28 h to 16 h by stages, with the constant reflux ratio of 200% at 32 ± 1 °C. It was found that the optimal HRT is 20 h with the removal efficiency of COD, NH4 + -N and TN in the steady phase averaging 79.1%, 99.5% and 93.2%, respectively. Meanwhile, the COD removed to TN removed ratio (CODrem /TNrem ) averaged 0.94, indicating that anammox was the main approach to TN removal. Microbial community analysis further revealed that the main nitrogen removal pathway in the first two anaerobic compartments was heterotrophic denitrification, while autotrophic partial nitritation - anammox process dominated the last two aerobic compartments. This study presented a cost-effective bioprocess for treating organic wastewater with high NH4 + -N and low COD/TN ratio. Graphical abstract: Image 1 Highlights: A HAOBR was constructed to treat manure-free piggery wastewater. Load removal of the HAOBR was evaluated by shortening HRT. HRT of 20 h was found as the optimal for COD, NH4 + -N and TN removal. TN removal in anaerobic compartments was mainly via heterotrophic denitrification. TN removal in aerobic compartments was mainly via partial nitritation-anammox.